Uses, abundance perception, and potential geographical distribution of Smilax aristolochiifolia Mill (SMILACACEAE) on the Totonacapan Region of Puebla, Mexico - José Espinoza-Pérez; César Reyes; Jesús Hernández-Ruíz; Maximino Díaz-Bautista; Francisco Ramos-López; Abel Espinoza-Gómez; Oscar Pérez-García (BMC, 2021)
Abstract Background In some regions of Mexico, edible wild plants have been displaced or eliminated from the traditional food systems, mainly by changes in land use, booming monoculture, herbicide use, and by changes among the new generations in the traditional foods and diets of indigenous populations. In the Totonacapan region of Puebla, the gradual change from the traditional acahual plantation to coffee-type agroecosystems has provoked the displacement of old-growth forests and the eradication of wild plants since 1970. One of the wild species which has been used in traditional medicine and food recipes by the Totonac culture is Smilax aristolochiifolia (SMILACACEAE), known as "kgentsililh". This species forms part of traditional Totonac recipes, in which the tender stems are still used in local medicine to treat menstrual pain, deal with dysentery, and prevent hair loss. According to the Maxent® Program, there are still potential areas with habitats suitable to promote its conservation in the Poblano Totonacapan. Methods We conducted 260 interviews with people in 13 locations in the northern Sierra of the State of Puebla. Variables taken into account in the interview related to the consumption frequency of the species, its abundance and distribution perception, reasons or arguments given by the Totonac indigenous population about the decreased presence of specimens of S. aristolochiifolia, its dates of collection, and the cutting prices of kgentsililh at the community level and in local markets. The relative abundance of S. aristolochiifolia was determined through 22 samples in 2ts of 600 m2. Later, its potential distribution in the state of Puebla was estimated using the Maxent® Program Ver. 3.3.3. Results Of the 260 Totonac families interviewed, 31% had stopped consuming kgentsililh. The residents reported that in the last 50 years the populations of this plant had diminished in the northern Sierra of the State of Puebla, mainly due to changes in land use, herbicide application, over-collection, and urban growth. In traditional medicine, the stem sap of S. aristolochiifolia is currently employed to help treat baldness, and the "tuberous root" or plant rhizome is used to prepare a tea infusion to treat dysentery. The cost of plant guides varies from 10.00 to 40.00 Mexican pesos for one bunch (around 0.5 to 2.00 US dollars), and every bundle consists of between 7 to 10 cuttings from 0.4 to 0.5 m long. From our 22 quadrats of sampling and collection of S. aristolochiifolia, we were able to recognize a total of 32 specimens. There is a considerable abundance of kgentsililh in acahual plantations and old-growth forests (evergreen lowland and mid-elevation perennial forest) concerning the coffee-type plantations and milpas. According to our analysis using the Maxent Program®, eight physical and climatic variables have a direct relationship to the potential distribution of the species. Conclusions Smilax aristolochiifolia is still a plant of socioeconomic importance, mainly because of its food value and its use in traditional medicine by indigenous families in Poblano Totonacapan. It is evident that the villagers perceive that in the last 50 years the species has decreased its population mainly due to land-use change, the application of herbicides to the different family production units, and climate change. At the moment, there is no knowledge about the methods of propagation of the species, and therefore there is no intention on the part of the population to conserve the species. However, it would be of great importance to generate a biocultural conservation strategy and take advantage of the results obtained from the potential geographic distribution area, since according to the Maxent® Program, there are still potential areas with habitat suitable to promote conservation in Poblano Totonacapan.